Implementation of Digital Transformation in the Mekaar Funding Disbursement Process at PT. Permodalan Nasional Madani Samarinda Branch - Yazdi Anugrah; Wilfridus B. Elu (Formosa Journal of Sustainable Research, 2023)
This study aims to find out and analyze how the application of the digital transformation process in the distribution of PT Mekaar product financing. Civil National Capital of Samarinda Branch and its effectiveness. This study uses a qualitative method with data collection tools through in-depth interviews to obtain information and analyze the business model. The research subjects were PNM Samarinda Branch Account Officers and customers of PNM Mekaar Samarinda Branch. The results showed that PNM Samarinda Branch had implemented digital transformation through the use of the PNMDigi application in the process of channeling PNM Mekaar financing. The implementation was effective and efficient because it assisted the Account Officer in speeding up the Mekaar PNM distribution process